Antinuclear Antibody-Positive Ticlopidine-Induced Hepatitis - Sander Jo Veldhuyzen van Zanten; C William McCormick (Canadian Journal of Gastroenterology)
Ticlopidine hydrochloride has been shown to reduce the risk of first or recurrent stroke in patients who have experienced a transient ischemic attack, reversible ischemic neurological deficit, recurrent stroke or first stroke. Severe liver dysfunction is a contraindication for its use. Increase in liver enzymes has been reported with use of this drug, but jaundice is rare. A case of severe ticlopidine-induced hepatitis that was associated with a marked increase in antinuclear antibody (ANA) levels is reported. Physicians prescribing ticlopidine hydrochloride should be aware that a potentially severe acute hepatitis associated with ANA positivity can occur. The drug should be discontinued if signs of liver dysfunction occur.